Peningkatan Kinerja Karyawan melalui Budaya Organisasi pada PT Huda Express - Eigis Yani Pramularso (Universitas Bina Sarana Informatika, 2018)
Abstract - Every organization faces internal and external challenges such as technological developments, global competition, and internal issues related to organizational policy. One of the potentials that the organization needs to optimize in facing the current challenges is the potential of human resources who understand and implement the organizational culture to produce the best performance for the achievement of organizational goals. This study aims to determine the effect of organizational culture on employee performance PT Huda Express. In this study the number of respondents as many as 30 employees. The data were collected by using questionnaires with data analysis using normality test, linearity test, simple regression analysis, t test, correlation coefficient, and coefficient of determination. The results showed that organizational culture has a positive and significant impact on employee performance of PT Huda Express. The magnitude of the correlation coefficient shows the amount of 0.408, it means the relationship of organizational culture to the employee's performance is quite strong. Coefficient of determination or R Squared = 0.166 which means organizational culture has a contribution to employee performance of 16.6% while the rest is influenced by other factors than organizational culture. Keywords: Organizational Culture, Employee Performance